Notice of Retraction: Research and Application of Multi-Node Communication and Energy Consumption Prediction Control in Underwater Acoustic Network - Jingguo Qu; Zilong Zhang; Yuhuan Cui; Jiahao Wang; George Mastorakis (IEEE Access)
Retracted.